Will Money Talk? Firm Bribery and Credit Access. Issue 1 (26th April 2018) - Qi, Shusen; Ongena, Steven
Abstract: We investigate whether corruption impedes firm growth by limiting access to bank credit. Our estimates demonstrate that access to credit tightens when a firm is more frequently involved in bribery practices and that bribery (most likely) causes this loss of access. We also find that the detrimental impact is mainly driven by supply‐side rather than demand‐side factors and that the loss of access is particularly strong when there are fewer foreign banks in the vicinity of the firm or when competition is either very low or very high in the local banking market. Finally, the bribery‐driven increase in financing obstacle significantly impedes future firm growth.